Low-Temperature Intermolecular Addition of RCF2Li Compounds to Various Carbonyl Electrophiles for a Practical Synthesis of CF2-Containing Building Blocks - Decostanzi, Mélanie; Campagne, Jean-Marc; Leclerc, Eric (Synthesis, 2016)
The addition of various RCF2Li compounds to a wide range of carbonyl electrophiles (aldehydes, ketones, acylsilanes, esters, and lactones) is reported. The reaction proceeds at very low temperature under Barbier conditions through a Br/Li exchange from the corresponding RCF2Br compounds. In contrast with existing methods that use more stable, but less reactive, organometallic species, there is efficient addition to esters, lactones and poorly reactive ketones.
Keywords: fluorine; organolithium; carbenoid; acylsilanes; ketones; esters; lactones